PENGARUH MEDIA PEMBELAJARAN EDUCANDY TERHADAP MOTIVASI BELAJAR SISWA KELAS IV PADA MATA PELAJARAN PENDIDIKAN PANCASILA DI SD NEGERI 1 WONOBOYO - Lestari, Ayu; Rispatiningsih, Dwi Maryani; Darma, Widia (Inteligensi : Jurnal Ilmu Pendidikan, 2024)
This study aims to determine whether there is an effect of Educandy learning media on the learning motivation of fourth grade students in Pancasila Education subjects at SD Negeri 1 Wonoboyo. This research is a quasi-experimental quantitative research, namely Non-Equivalent Control Group Design, which has two groups of subjects for the experimental class and the control class. Involving as many as 36 students. Data collection techniques were observation, questionnaires, interviews, and documentation. Data analysis is normality test, homogeneity test, and independent sample t-test. The use of learning motivation questionnaires to determine student learning motivation at the beginning and end. The results of the initial motivation questionnaire for the control and experimental classes respectively obtained an average value of 68.33 and 66.44, while the results of the final motivation questionnaire were 61.11 and 72.78. The hypothesis test conducted was obtained when the significance value (2-tailed) was 0.000. The conclusion obtained is if there is an effect of Educandy learning media on the learning motivation of SD Negeri 1 Wonoboyo students.